Studying shadow page cache to improve isolated drivers' performance. (8th February 2017) - Zheng, Hao; Zhu, Zhengdong; Dong, Xiaoshe; Chen, Baoke; Liu, Chengzhe
Summary: Using virtualization technology, users can reuse various existing operating systems and drivers to customize their application environments. However, faults that exist in the reused drivers threaten the users' customized environments. Chariot has been proposed to solve this problem. It isolates a driver by monitoring its real‐time performance and examining the correctness of its write operations. To capture the write operations, we found that it needs to keep the write permissions of shadow pages as read‐only, which may cause many page faults in the virtual machine monitor and has adversely affect the driver's performance. To address this, we propose a new algorithm that uses the shadow page cache to remit the page faults, based on the principle of delaying the closing of the write permissions of frequently accessed shadow pages. Experimental results show that using these shadow page caches, we can greatly the performance of isolated drivers without significantly impacting Chariot's isolation efficiency.